2011
DOI: 10.1103/physreva.83.053814
|View full text |Cite
|
Sign up to set email alerts
|

Sudden vanishing and reappearance of nonclassical effects: General occurrence of finite-time decays and periodic vanishings of nonclassicality and entanglement witnesses

Abstract: Analyses of phenomena exhibiting finite-time decay of quantum entanglement have recently attracted considerable attention. Such decay is often referred to as sudden vanishing (or sudden death) of entanglement, which can be followed by its sudden reappearance (or sudden rebirth). We analyze various finite-time decays (for dissipative systems) and analogous periodic vanishings (for unitary systems) of nonclassical correlations as described by violations of classical inequalities and the corresponding nonclassica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…The commonly accepted formal criterion for distinguishing nonclassical states from classical ones is expressed as follows [10,11,25,26]: A quantum state is nonclassical if its Glauber-Sudarshan P function fails to have the properties of a probability density. Alternatively, several operational criteria for nonclassicality of either single-mode [25][26][27] or multimode [28][29][30] fields have been revealed. Their derivations are based either on field's moments [28,30,31] or on direct reconstruction of quasidistributions of integrated intensities [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The commonly accepted formal criterion for distinguishing nonclassical states from classical ones is expressed as follows [10,11,25,26]: A quantum state is nonclassical if its Glauber-Sudarshan P function fails to have the properties of a probability density. Alternatively, several operational criteria for nonclassicality of either single-mode [25][26][27] or multimode [28][29][30] fields have been revealed. Their derivations are based either on field's moments [28,30,31] or on direct reconstruction of quasidistributions of integrated intensities [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The weak interaction has been parameterized as J = J 0 cos(ϕ) i K = J 0 sin(ϕ), where ϕ = −0.358π and J 0 turns into the range 0-0.05. For simplicity, we have assumed that q = 0, and hence, the wave function | Ψ (t) is fully described by the probability amplitudes (8) and (9). For the chosen here values of the parameters, it is easy to find the period T 0 which is given by T 0 = 2π/(3|J − K |) ≈ 105.…”
Section: Weak Interactionmentioning
confidence: 99%
“…A key question of the solid-state quantum information processing is whether an engineered system could display multipartite states with designed quantum properties B Artur Barasiński a.barasinski@if.uz.zgora.pl 1 Quantum Optics and Engineering Division, Institute of Physics, University of Zielona Góra, Z. Szafrana 4a, 65-516 Zielona Gora, Poland necessary for many spectacular phenomena of quantum world, such as quantum teleportation [1][2][3][4][5], quantum cryptography [6,7] or in general, indicating for the quantumness of physical systems [8]. In particular, the multi-qudit entanglement (which starts at the tripartite entanglement) necessary for quantum error correction effect has been recently gaining increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Song et al [19] and Ali [20,21] reported that free entangled states can evolve into nondistillable (bound entangled or separable) states in finite time under local noise, which is named distillability sudden death (DSD). What is more, through calculating the spin parameters of a spin ensemble in a collective initial state under three different decoherence channels, Wang et al [22,23] found that spin squeezing can suddenly vanish with different lifetimes for some decoherence channels. In a word, the sudden death phenomena mentioned above are all caused by different channels of decoherence.…”
mentioning
confidence: 99%